Gray matter bases of psychotic features in adult bipolar disorder: A systematic review and voxel‐based meta‐analysis of neuroimaging studies. Issue 12 (10th August 2018) - Wang, Xiuli; Tian, Fangfang; Wang, Song; Cheng, Bochao; Qiu, Lihua; He, Manxi; Wang, Hongming; Duan, Mingjun; Dai, Jing; Jia, Zhiyun
Abstract: Psychotic bipolar disorder (P‐BD) is a specific subset that presents greater risk of relapse and worse outcomes than nonpsychotic bipolar disorder (NP‐BD). To explore the neuroanatomical bases of psychotic dimension in bipolar disorder (BD), a systematic review was carried out based on the gray matter volume (GMV) among P‐BD and NP‐BD patients and healthy controls (HC). Further, we conducted a meta‐analysis of GMV differences between P‐BD patients and HC using a whole‐brain imaging approach. Our review revealed that P‐BD patients exhibited smaller GMVs mainly in the prefronto‐temporal and cingulate cortices, the precentral gyrus, and insula relative to HC both qualitatively and quantitatively. Qualitatively the comparison between P‐BD and NP‐BD patients suggested inconsistent GMV alterations mainly involving the prefrontal cortex, while NP‐BD patients showed GMV deficits in local regions compared with HC. The higher proportions of female patients and patients taking psychotropic medication in P‐BD and P‐BD type I were associated with smaller GMV in the right precentral gyrus, and the right insula, respectively. In conclusions, psychosis in BD might be associated with specific cortical GMV deficits. Gender and psychotropic medication might have effects on the regional GMVs in P‐BD patients. It is necessary to distinguish psychotic dimension in neuroimaging studies of BD.